IDENTIFIKASI DIRI MELALUI SIMBOL-SIMBOL KOMUNIKASI (Studi Interaksionisme Simbolik Komunitas Pemakai Narkoba Di DKI Jakarta) - Edison Hutapea (Universitas Bunda Mulia, 2016)
The attractive reality narcotic consumption is the interaction amongs the user. The interaction isindicated by nonverbal communication via symbols that understanable solely by user community.There is unanimous by their own to give the meaning of symbols, because this is black market andillegal. The communications symbols is practised differently in evefry area because evade the law. Itmeans every area as region construct the reality in different way. This is based on the fact thatnarcotic consumer community has sight saliding to keep their mistery, more over new comes unable tointeract directly. This research aim to descript symbols used Narcotic consumer community in DKIJakarta to represent to become the reality. Based on the phenomenalogist theory from Alfred Schutz,constructivism from Berger and symbolis interactive from Mead and Cooley. Research resultexpressed that : Unanimous is made to give the meaning, constricted only to certain area, to presentthe symbols understandable wider it means their transactions secrecy widely open. Solidity of narcoticconsumer will be loose when the region of understable symbolis wider.Keywords : Symbol, Meaning, Self Concept and Community.